Koreografi Tari Pasambahan Sanggar Nan Gombang di Painan Kabupaten Pesisir Selatan - Triwana Triwana; Susmiarti Susmiarti (FBS Universitas Negeri Padang, 2023)
This study aims to reveal and describe the Choreography of pasambahan dance in Sanggar Nan Gombang in Painan, Pesisir Selatan Regency. This type of research is qualitative research with descriptive methods. This research instrument is the researcher himself and is assisted by supporting instruments such as stationery, books, cellphones, digital cameras. The data in this study used primary data and secondary data. Data collection techniques are carried out by means of literature studies, observations, interviews, documentation. The steps of analyzing data are data collection, data reduction, data presentation and drawing conclusions. The results showed that pasambahan dance consists of choreographic elements which include themes, movements, upper design, floor design, music design, dramatic design, process, equipment, and group choreography. The theme of pasambahan dance is welcoming distinguished guests. The movements of the Pasambahan dance consist of 24 kinds of movements. In the upper design listed from the Pasambahan dance, it is more dominant to use angular, horizontal, low, and vertical upper designs. In this Pasambahan dance floor design, it is developed from a straight line, curved and left oblong. Pasambahan dance music design uses musical instruments such as Talempong, Bansi, Gandang, Violin, Saluang, and Guitar Bass. The dramatic design of Pasambahan dance has an atmosphere of excitement of a host who welcomes guests who come to visit. The process of this Pasambahan dance starts from the idea possessed by the choreographer and is expressed in the form of motion that exists in the elements of choreography, as well as the property of carano that is used more predominantly in unison interactions.